Forest resources and their nutritive worth for arid livestock - Patidar, Tejkaran; Bairwa, Mukesh; Mathur, B. K.; Tewari, J. C. (Indian Farming, 2018)
India is highest milk producing country in world but fodder shortages may knock India off its position as the words’ top milk producer. The milk productivity of India’s livestock is less than half (48%) of the global average: 987 litre per lactation compared to the global average of 2,038 kg/lactation. The availability and quality of fodder has a direct bearing on the quantity and quality of milk productivity. All the three states that topped milk productivity in g/day in Rajasthan, Haryana and Punjab had earmarked more than 10% of their cultivable land for pastures, according to 2015 State of India’s Livelihoods Report. Currently all three types of fodder (green, dry and concentrates) are in short supply. Considering the demand of milk, land under fodder production needs to be increased. Shortages are forcing to locate new source of fodder. In this situation forest resources may play an important role to complete the fodder requirement.